Mechanisms of palmitic acid-conjugated antisense oligonucleotide distribution in mice. Issue 8 (17th March 2020) - Chappell, Alfred E; Gaus, Hans J; Berdeja, Andres; Gupta, Ruchi; Jo, Minji; Prakash, Thazha P; Oestergaard, Michael; Swayze, Eric E; Seth, Punit P
Abstract: Conjugation of antisense oligonucleotide (ASO) with a variety of distinct lipophilic moieties like fatty acids and cholesterol increases ASO accumulation and activity in multiple tissues. While lipid conjugation increases tissue exposure in mice and reduces excretion of ASO in urine, histological review of skeletal and cardiac muscle indicates that the increased tissue accumulation of lipid conjugated ASO is isolated to the interstitium. Administration of palmitic acid-conjugated ASO (Palm-ASO) in mice results in a rapid and substantial accumulation in the interstitium of muscle tissue followed by relatively rapid clearance and only slight increases in intracellular accumulation in myocytes. We propose a model whereby increased affinity for lipid particles, albumin, and other plasma proteins by lipid-conjugation facilitates ASO transport across endothelial barriers into tissue interstitium. However, this increased affinity for lipid particles and plasma proteins also facilitates the transport of ASO from the interstitium to the lymph and back into circulation. The cumulative effect is only a slight (∼2-fold) increase in tissue accumulation and similar increase in ASO activity. To support this proposal, we demonstrate that the activity of lipid conjugated ASO was reduced in two mouse models with defects in endothelial transport of macromolecules: caveolin-1 knockout (Cav1 −/− ) and FcRn knockout (FcRn −/− ).